Newcastle Disease Virus Nonstructural V Protein Upregulates SOCS3 Expression to Facilitate Viral Replication Depending on the MEK/ERK Pathway - Wang, Xiangwei; Jia, Yanqing; Ren, Juan; Huo, Na; Liu, Haijin; Xiao, Sa; Wang, Xinglong; Yang, Zengqi (Frontiers in Cellular and Infection Microbiology, 2019)
Newcastle disease virus (NDV) causes serious economic losses to the poultry industry. In our previous study, we found that NDV induced a strong innate immune response in the chicken embryo and bursa of Fabricius (BF). However, the underlying mechanisms by which NDV escape the host innate immunity are not well understood. The suppressor of cytokine signaling 3 (SOCS3) inhibits type I interferon-dependent antiviral signaling pathway by utilizing a feedback loop. In this study, we analysised the transcriptome data of the chicken embryo and BF infected with NDV, and found the significant upregulation of SOCS3. Next, we demonstrated that NDV infection and nonstructural V protein induced the up-regulation of SOCS3. Furthermore, we showed that overexpression of SOCS3 facilitated viral replication and reduced the expression of phosphorylation STAT1, MX1 and OASL, while inhibition of SOCS3 with siRNAs reduced virus replication and promoted the expression of phosphorylation STAT1, MX1 and OASL. Finally, we demonstrated that MEK/ERK signaling pathway was involved in the expression of SOCS3 mediated by NDV infection and V protein transfection, and using specific inhibitor U0126 to block this signaling pathway attenuated SOCS3 expression and inhibited NDV replication through promoting the expression of type I interferon, OASL and MX1. Taken together, these data demonstrate that NDV infection and NDV nonstructural V protein activates the expression of SOCS3 at the mRNA and protein level through a mechanism depending on MEK/ERK signaling pathway, which benefits virus replication.